Aerospace series. Aluminium alloy AL-P2024. AlCu4Mg1. T3511. Extruded bars and sections. 1, 2 mm ≤ De ≤ 160 mm with peripheral coarse grain control. (30th November 2015) - British Standards Institution
No abstract available